2020
DOI: 10.3390/ijerph17238949
|View full text |Cite
|
Sign up to set email alerts
|

Residential Exposure to PM2.5 Components and Risk of Childhood Non-Hodgkin Lymphoma in Denmark: A Nationwide Register-Based Case-Control Study

Abstract: In a recent study, we observed an increased risk of childhood non-Hodgkin lymphoma (NHL) associated with exposure to fine atmospheric particulate matter (PM2.5) and black carbon (BC). In this nationwide register-based case-control study, we focus on specific components of PM2.5 in relation to childhood NHL in Denmark (1981–2013) by identifying all incidents of childhood NHL cases in the Danish Cancer Registry (n = 170) and four (cancer-free) randomly selected controls matched by date of birth and sex. We appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Furthermore, a Spanish case–control study on bladder cancer risk did not find an association between PM 2.5 and UCC 57 . In contrast, NHL has been significantly associated with higher PM 2.5 concentrations, particularly black carbon and volatile organics 58,59 . These subsets of PM 2.5 were not available in the EPA database for our study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, a Spanish case–control study on bladder cancer risk did not find an association between PM 2.5 and UCC 57 . In contrast, NHL has been significantly associated with higher PM 2.5 concentrations, particularly black carbon and volatile organics 58,59 . These subsets of PM 2.5 were not available in the EPA database for our study.…”
Section: Discussioncontrasting
confidence: 54%
“…57 In contrast, NHL has been significantly associated with higher PM 2.5 concentrations, particularly black carbon and volatile organics. 58,59 These subsets of PM 2.5 were not available in the EPA database for our study. In addition, EPA data were relatively sparse for PM 2.5 concentrations, so our negative findings may have been due in part to missing EPA data and inadequate power.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Taj et al ( 15 ) demonstrated that PM 2.5 components were more positively associated with AML [OR = 1.14; interquartile range (IQR) = 1.00–1.29] than chronic myeloid leukemia and chronic lymphocytic leukemia. The effects of PM 2.5 and other components are related not only to adult leukemia but also to childhood hematological malignancy as reported in studies by Lavigne et al ( 19 ) and Hvidtfeldt et al ( 16 ). Consistently, Lavigne et al ( 19 ) demonstrated the relationship between traffic air pollution exposure in approximately a million pregnant women and the incidence of childhood acute lymphoblastic leukemia (ALL) in their offspring.…”
Section: Resultsmentioning
confidence: 70%
“…This study design showed the strongest relationship between fetal exposure to air pollution during pregnancy and leukemia in the first year of age. A study by Hvidtfeldt et al ( 16 ) showed a high OR ratio of 2.05 (IQR = 1.10–3.38) in childhood non-Hodgkin lymphoma with exposure to PM 2.5 . Molecular epidemiology studies suggested that DNA methylation of the leukemic gene was positively correlated with exposure to environmental toxins ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation